Walking with Ines – Sensing Urban Transformation - Leinonen Päivi; Lillbroända-Annala Sanna (Ethnologia Fennica, 2026)
This article examines a walk-along interview conducted in the new district of Linnakaupunki in Turku, Finland. We aim to find out what elements in the urban environment affect the well-being of one resident and how she perceives these factors along the route she chose. In this study, we pay attention to the method itself: how does our method of a walk-along interview, conducted with a wearable action camera, help us distinguish these different factors of well-being? We view the walk-along interviews as an entanglement where the method, the technique used, and the bodily senses intertwine.
In our study, the walk creates a frame for the interview allowing place-related thoughts to arise in a specific moment. Walking makes the connection to places immediate. The Linnakaupunki area combines different time layers, creating the spirit and atmosphere of the place. The wearable camera can document the route in detail, record time levels and landscape changes, and capture the interviewee’s affective experiences and responses.